Development and validation of scales measuring self-efficacy and behavioral capability in managing common medical emergencies in dental clinics - Yasmine N. Alawaji; Hussam M. Alqahtani; Abdulmohsen Alfadley; Aram Alshehri; Ali Aboalela; Sahr H. Altuwaijri; Farraj Albalawi; Sara A. Kalagi; Abdulrhman Alghamdi; Abdullah Alshibani; Meshal Alharbi; Meshary Binhotan; et al. (BMC Medical Education)
Abstract Objectives Managing medical emergencies is a critical skill for dental professionals, yet many dental practitioners and trainees face challenges in developing the competence required for effective management. This study aimed to develop and validate scales that measures self-efficacy (i.e., perceived confidence in performing a behavior) and behavioral capability (i.e., knowing what and how to do a behavior) in handling common medical emergencies in dental clinics and to identify factors influencing these outcomes. Methods Two newly created 13-item self-efficacy and 19-item behavioral capability were validated for their construct validity and psychometric properties. Univariate linear regression analyses were used to identify factors associated with self-efficacy and behavioral capability. Results A total of 140 students/interns were included, of which 73 students (52.1%) were females. The internal consistency of the scales using Cronbach alpha was 0.93 for self-efficacy and 0.88 for behavioral capability. Using confirmatory factor analysis, the internal structure of self-efficacy scale had a single latent variable and 13 items, and the behavioral capability scale had a single latent variable and 19 items. The final models of both scales had adequate goodness of fit as indicated by the indices including standardized root mean squared residual < 0.08, root mean squared error of approximation (RMSEA) < 0.08, and upper bound of RMSEA 90% confidence interval < 0.10. The self-efficacy was lower in 4th year students and interns by mean reduction of 17.6 points (95% CI: -27.4, -7.7) and 18.2 points (95% CI: -32.6, -3.8) respectively, compared to 3rd year students. The mean reduction of self-efficacy in females was 12.5 points (95% CI: -3.4, -21.5) compared to males. Dental trainees with higher graduate point average (GPA) had a mean decrease in self-efficacy by 9.9 points (95% CI: -19.1, -0.6). Time since last basic life support (BLS) certification had a dose response association with self-efficacy; having BLS in 6 to < 12 months and ≥ 12 months had mean reduction of self-efficacy by 14.6 points (95% CI: -29.2, -0.1) and 19.9 points (95% CI: -30.7, -9.1) respectively, compared to < 6 months. The behavioral capability was significantly higher in 4th year students and interns with a mean increase by 4.1 scores (95% CI: 2.0, 6.3) and 3.8 scores (95% CI: 0.4, 7.2) respectively, compared to 3rd year students. Having last BLS certification in ≥ 12 months had higher behavioral capability by 4.8 scores (95% CI: 2.6, 7.0) compared to < 6 months. Conclusions Using the two newly developed and validated scales, the self-efficacy and behavioral capability to manage medical emergencies in dental clinic were generally low among dental trainees. We recommend tailoring the medical emergency management training to dental settings and renewing the BLS certification more frequently to enhance the self-efficacy and behavioral capability. For future studies, we recommend externally validating the scales and evaluating their sensitivity to changes in students training. Clinical trial number Not applicable.